Mediating Role of Green Entrepreneurial Orientation Between Entrepreneurship Education and Academic Support on Green Entrepreneurial Intention - Ahmad Sehabuddin; Joko Widodo; Indri Murniawaty; Risanda Alirastra Budiantoro (Economics Education Department Universitas Negeri Semarang, 2024)
This study aims to analyze the impact of entrepreneurship education and academic support on green entrepreneurial intention, analyzing the role of mediation green entrepreneurial orientation between entrepreneurship education and academic support of green entrepreneurial intention. This study is a quantitative study. The sample of this study were 395 student Faculty of Economics and Business at three universities in Indonesia, namely the Universitas Indonesia (UI), Universitas Negeri Semarang (UNNES), and the Institut Pertanian Bogor (IPB). Analysis techniques use modeling Structural Equation Models. The results of the study state that entrepreneurship education and academic support influence green entrepreneurial intention. Besides that, green entrepreneurial orientation can mediate between entrepreneurship education and educational support for green entrepreneurial intention. The implications of this study are to help educational institutions in designing programs from the curriculum side, increasing academic support and collaboration with industries that focus on green entrepreneurship. In this context, educational institutions are more effective in encouraging students to have the intention to engage in green entrepreneurship, so that they can contribute to sustainable development.